The role of universities in global development: present and future - Ilyin, Ilya V. (Opción, 2020)
Based on current trends and demographic forecasts, the present paper assesses the role of universities in global development and its dynamics for the coming decades. The role of universities is considered in view of changing the demographic situation and the global convergence process, that is, the gradual approximation of the development level of advanced and developing countries of the world. It is shown that demographic processes, economic development and global convergence have a key impact on the development of universities. It has been shown that digitalization is no longer a challenge for a traditional university.